Strengthening The Legislative Function of Indonesia’s Regional Representative Council: Normative and Evaluative Performance Analysis - Umaroh, Abi; Ananta, Radite Ranggi (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2025)
The implementation of the legislative function of the House of Regional Representatives (DPD) of the Republic of Indonesia in regional development faces serious challenges due to the limited authority it has. DPD, which is supposed to be the mouthpiece of the regional community, in practice functions more as a complement to the House of Representatives (DPR) in the Indonesian parliamentary system. This study aims to analyze the implementation of the legislative function of DPD during the working period of 2020-2024, as well as to identify solutions that can strengthen the role of DPD in the legislative system. The method used in this research is field research with a normative juridical qualitative approach. The data sources of this research include primary data, secondary data, and legal materials. Data retrieval techniques are taken through interviews as well as documentation and analyzed using inductive descriptive techniques. The results indicate that the amendment to Article 20 Paragraph (1) and Article 22D Paragraph (2) of the Constitution of the Republic of Indonesia is necessary as a strategic step to strengthen the legislative authority of DPD. By strengthening through reformulation of these articles, the role of DPD can run more optimally and substantively in encouraging regional development.